Optimizing the Irrigation Water Needsof Banana Plants at PT. Nusantara Segar Abadi Jembrana-Bali - Juliawan, I Gede Nantan; Tika, I Wayan; Arthawan, I Gusti Ketut Arya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The water availability does not meet the water requirement of banana plants has been the main issue causing a non-optimal production. Presumably, it is due to the application of pump power. Therefore, it is necessary to analyze the amount of pump power needed to meet the irrigation water needs. The purposes of this study were to determine the pump power requirement and to design a pump application schedule to meet the irrigation water requirement of banana plants. Primary data is obtained by measuring the available discharge.Secondary data was obtained from BMKG Jembrana Regency. This study employed the principle of water balance. The collected data was then analyzed to determine the amount of power needed when the shortage of water occurred. The results showed that the pump power requirement for each banana cultivation period was 3.1 kW, March-April 5.0 kW, May-June 11.0 kW, July-August and September-October of 16.5 kW, and November-December of 0 kW. The Pump usage schedule at PT. Nusantara Segar Abadi in the January-February period requires one pump unit with an operating time of 0.8 hours, March-April requires one pump unit with an operating time of 6.4 hours, May-June requires two pump units with an operating time of 8, 7 hours, the period of July-August and September-October requires three pump units with an operating time of 10.5 hours and 10.2 hours, and the period November-December does not require a pump.